Anda di halaman 1dari 6

# Math021, week 5

Example 5.1 Evaluate the derivative of the function f (x) = solution: For h = 0 and x = 0,
f (x+h)f (x) h 1 1 1 =h [ x+ h x] x(x+h) = hx(x+h) = x(x1 +h) .

## So, f (x) = lim

h 0

1 1 = 2 x(x + h) x

for all x = 0. Example 5.2 Evaluate the derivative of the function f (x) = x for all numbers x > 0. solution: For h = 0 and x > 0,
f (x+h)f (x) h x+h x = h x)( x+h+ x) = ( x+h h( x+h+ x) (x+h)x = h( x+h+ x) 1 = (x+h+x) .

So,

1 1 f (x) = lim = h0 ( x + h + 2 x x)

for all x > 0. Example 5.3 Evaluate the derivative of f at 0 if f (x) = |x| for all numbers x 1

soltion: For h = 0,
f (0+h)f (0) h | = |h h . | But limh0 |h h does not exist (why?). So, the function f does not have a derivative at 0. Sometimes, we say that f is not dierentiable at 0.

Theorem 5.4 A dierentiable function is continuous. proof: dicult Standard Formula for Derivatives Theorem 5.5 If a is a number and f (x) = a for all x. Then, f (x) = 0. proof: For h = 0 and all x,
f (x+h)f (x) h a = a h

=0 So,

f (x) = lim 0 = 0.
h0

Theorem 5.6 If n is a positive integer and f (x) = xn for all x. Then, f (x) = nxn1 . proof: For h = 0 and all x,
f (x+h)f (x) h n xn = (x+h) h n1

= (x + h ) So,

h 0

## Theorem 5.7 If f and g are functions, (f + g ) = f + g . proof: For h = 0 and all x,

(f +g )(x+h)(f +g )(x) h )(f (x)+g (x)) = f (x+h)+g(x+h h )f (x) )g (x) = f (x+hh + g(x+hh

So, f (x) )f (x) )g (x) = limh0 f (x+hh + g(x+hh )f (x) )g (x) = limh0 f (x+hh + limh0 g(x+hh = f (x) + g (x). Theorem 5.8 If f and g are functions, (f g ) = f g . proof: omitted Theorem 5.9 If f is a functions and a is a number, (af ) = a(f ). proof: For h = 0 and all x,
(af )(x+h)(af )(x) h a(f (x)) = a(f (x+h)) h )f (x) = a f (x+hh

So, f (x) )f (x) = limh0 a f (x+hh )f (x) = a limh0 f (x+hh = a(f (x)). Example 5.10 Let f (x) = 1 + 2x + 3x2 + 4x3 for all x. Evaluate the derivative of f . solution: The The The The derivative derivative derivative derivative of of of of 1 is 0 2x is 2 times the derivative of x which is 2 3x2 is 3 times the derivative of x2 which is 6x 4x3 is 4 times the derivative of x3 which is 12x2

So, the derivative of f is f (x) = 2 + 6x + 12x2 . Theorem 5.11 (Product Rule) If f and g are functions, (f g ) = f g + f g . proof: For h = 0 and all x,
(f g )(x+h)(f g )(x) h )(f (x)g (x)) = f (x+h)g(x+h h f (x+h)g (x+h)f (x+h)g (x)+f (x+h)g (x)f (x)g (x) = h )g (x) )f (x) = f (x + h) g(x+hh + g (x) f (x+hh

So, (f g ) (x) )g (x) )f (x) = limh0 f (x + h) g(x+hh + g (x) f (x+hh g (x+h)g (x) = limh0 f (x + h) limh0 + g (x) limh0 h = f (x)g (x) + f (x)g (x).

f (x+h)f (x) h

## Theorem 5.12 (Quotient Rule) If f and g are functions, ( f g) =

gf f g g2

proof: Since f = f g g . Taking derivatives on both sides of the equation by product rule yields f f f =( )g+ g. g g Rearrange the equation and we get f gf f g ( ) = . g g2 Example 5.13 If f (x) =
1 x7

## for all x. Evaluate the derivative of f .

solution: The derivative of f is, by the quotient rule, f (x) = (0)x7 (1)7x6 7 = 8. (x7 )2 x

Remark 5.14 In a similar way, we are able to show that if n is a negative integer, the derivative of f (x) = xn is f (x) = nxn1 . Example 5.15 Find the line tangent to the graph of f (x) = (1, 2).
2 x3

at the point

solution: 6 Since f (x) = 2(3)x4 = x 4 , we have f (1) = 6. The line tangent to the graph of f at (1, 2) is the straight line with slope f (1) = 6 which passing through (1, 2). That is, the line whose dening equation is y 2 = 6(x 1) or y = 6x + 8. Theorem 5.16 If f (x) = sin x for all x. Then, f (x) = cos x. proof: For h = 0 and all x,
f (x+h)f (x) h )sin x = sin(x+h h h h h sin(x+ h 2 + 2 )sin(x+ 2 2 ) = h h h h sin(x+ 2 ) cos 2 +cos(x+ 2 ) sin

= cos(x + h 2)

sin
h 2

h 2

. 4

sin
h 2 h 2

## = limh0 cos(x + h 2 ) limh0

sin
h 2

h 2

Theorem 5.17 If f (x) = cos x for all x. Then, f (x) = sin x. proof: similar Theorem 5.18 If f (x) = tan x for all x. Then, f (x) = sec2 x. proof: Since tan x =
sin x cos x .

We take derivative by quotient rule and get f (x) = cos x cos x + sin x sin x = sec2 x. cos2 x

Theorem 5.19 If f (x) = cot x for all x. Then, f (x) = csc2 x. proof: Since cot x =
cos x sin x .

We take derivative by quotient rule and get sin x sin x cos x cos x = csc2 x. sin2 x

f (x) =

Theorem 5.20 If f (x) = sec x for all x. Then, f (x) = tan x sec x. proof: Since sec x =
1 cos x .

We take derivative by quotient rule and get f (x) = 0 cos x + 1 sin x = tan x sec x. cos2 x

Theorem 5.21 If f (x) = csc x for all x. Then, f (x) = cot x csc x. proof: Since csc x =
1 sin x .

We take derivative by quotient rule and get f (x) = 0 sin x 1 cos x = cot x csc x. sin2 x lim

## Denition 5.22 The limit

ah 1 h0 h is increasing in a. It is 0 when a = 1 and the limit is big provided that a is suciently large. Dene e to be the number such that eh 1 = 1. h0 h lim 5

Theorem 5.23 If f (x) = ex for all x. Then, f (x) = ex . proof: f (x) )f (x) = limh0 f (x+hh x+h x = limh0 e he x h x = lim h 0 e e he h 1 = ex limh0 e h x =e .